2022
DOI: 10.3389/fpubh.2022.904550
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Post-traumatic Stress Disorder Status Among Healthcare Workers and Its Impact on Their Mental Health During the Crisis of COVID-19: A Cross-Sectional Study

Abstract: ObjectiveAfter the unprecedented coronavirus disease 2019 (COVID-19) outbreak, the health status of the general population has suffered a huge threat, and the mental health of front-line healthcare providers has also encountered great challenges. Therefore, this study aims to: (1) investigate the prevalence and influencing factors of post-traumatic stress disorder (PTSD) among healthcare providers, and (2) verify the moderating role of self-efficacy in the influence of PTSD on mental health.MethodsA cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…These findings align, particularly with what has been reported by medical professionals and nurses in the context of the COVID-19 pandemic, given the nature of their work (caring for critical patients, frontline work, etc.) [55].…”
Section: Principal Resultsmentioning
confidence: 99%
“…These findings align, particularly with what has been reported by medical professionals and nurses in the context of the COVID-19 pandemic, given the nature of their work (caring for critical patients, frontline work, etc.) [55].…”
Section: Principal Resultsmentioning
confidence: 99%
“…Another emerging area of interest is PTSD following the COVID‐19 pandemic. Multiple studies have reported on PTSD diagnoses in COVID‐19 survivors (Chang & Park, 2020; Tarsitani et al., 2021) as well as among health care workers treating COVID‐19 patients (Yang et al., 2022; B. Yu et al., 2022). It is likely that PTSD prevalence and its association with health outcomes (e.g., stroke) is underestimated due to a lack of the proper infrastructure for data collection on PTSD exposure outside of the veteran population or WTC attack survivors in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Another emerging area of interest is PTSD following the COVID-19 pandemic. Multiple studies have reported on PTSD diagnoses in COVID-19 survivors (Chang & Park, 2020;Tarsitani et al, 2021) as well as among health care workers treating COVID-19 patients (Yang et al, 2022;B. Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The choice of assessment tools can influence reported prevalence rates, emphasizing the importance of standardized and culturally sensitive measures to capture the true extent of PTSD in different populations. PTSD varies widely, with a lifetime prevalence ranging from 6.1 to 9.2% in national samples ( 42 , 47 , 48 ). In the United States, the 1 year prevalence of PTSD was estimated at 6.7% among male veterans and 11.7% among female veterans, and the lifetime prevalence was reported to range from 3.4 to 26.9% among civilians.…”
Section: Introductionmentioning
confidence: 99%
“…Factors, such as female sex, lower income, younger age, and behavioral health conditions, were identified as risk factors for PTSD ( 47 , 48 ). These findings highlight the importance of understanding significant moderators of PTSD prevalence for tailoring interventions and support strategies for those at risk of or experiencing PTSD.…”
Section: Introductionmentioning
confidence: 99%